2016
DOI: 10.1039/c6sm00637j
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte/surfactant films spread from neutral aggregates

Abstract: We describe a new methodology to prepare loaded polyelectrolyte/surfactant films at the air/water interface by exploiting Marangoni spreading resulting from the dynamic dissociation of hydrophobic neutral aggregates dispensed from an aqueous dispersion. The system studied is mixtures of poly(sodium styrene sulfonate) with dodecyl trimethylammonium bromide. Our approach results in the interfacial confinement of more than one third of the macromolecules in the system even though they are not even surface-active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(96 citation statements)
references
References 52 publications
2
92
2
Order By: Relevance
“…While this procedure may be considered unconventional, it was necessitated by the challenge to quantify extremely small changes in the experimental data with a total interfacial thickness of less than 20 Å and weakly scattering drug molecules to give physically meaningful results. The reason why we could not use the low-Q compositional analysis method developed recently on FIGARO 32 where the interfacial composition is solved accurately by fast measurements only at low Q in the two isotopic contrasts involving ACMW, was because of the low SLD of the drug in the present study.…”
Section: Snr Compositional Analysismentioning
confidence: 97%
“…While this procedure may be considered unconventional, it was necessitated by the challenge to quantify extremely small changes in the experimental data with a total interfacial thickness of less than 20 Å and weakly scattering drug molecules to give physically meaningful results. The reason why we could not use the low-Q compositional analysis method developed recently on FIGARO 32 where the interfacial composition is solved accurately by fast measurements only at low Q in the two isotopic contrasts involving ACMW, was because of the low SLD of the drug in the present study.…”
Section: Snr Compositional Analysismentioning
confidence: 97%
“…First, a low-Q analysis was deployed to follow the compositional changes over time. In this approach, the low-Q data were reduced over a restricted Q-range of 0.01-0.03 Å -1 to minimize the influence of details of the structural model on the fitted lipid surface concentrations or peptide binding (31,32). The samples used were cm-DPPC, d-DPPC, and cm-DPPG and d-DPPG, respectively, measured in NRW, before and after injecting the G 4 peptide, where the term 'cm' refers to the lipid chains that were 'contrast matched' to give zero SLD.…”
Section: Neutron Reflectivitymentioning
confidence: 99%
“…In contrast, the signal of NR relies on statistical counting from the interface. It was found that by measuring the binding of the G4 peptide onto either 'cm' or 'd' lipid monolayers in NRW, each run could be taken in 4 min, but the reflectivity must be recorded over the high flux range at the low incidence angle of the neutron beam(32). This was achieved by undertaking the reflectivity measurements over the low-Q range.In order to calculate the adsorbed amount, we have applied Eq.…”
mentioning
confidence: 99%
“…Recent advances in instrumentation have meant that it is now possible to resolve the surface excess of a single deuterated species on the second time scale and the composition of a binary mixture involving only one deuterated component on the minute time scale. 3,4,5 Nowadays, NR provides routine insight into complex systems in soft matter and biology. 6,7 It is most common to treat experimental reflectivity data through fitting models using the optical matrix or Parratt formulism for stratified media.…”
Section: Introductionmentioning
confidence: 99%